Effects of Melamine and Cyanuric Acid on Embryo‐Fetal Development in Rats. (9th December 2013) - Kim, Sung‐Hwan; Lee, In‐Chul; Baek, Hyung‐Seon; No, Kyeong‐Woo; Shin, Dong‐Ho; Moon, Changjong; Kim, Sung‐Ho; Park, Seung‐Chun; Kim, Jong‐Choon
<x xml:space="preserve">Abstract</x> After the outbreak of acute renal failure associated with melamine‐contaminated pet food, melamine and melamine‐related compounds have become of great interest from a toxicologic perspective. We investigated the potential effects of melamine in combination with cyanuric acid (M + CA, 1:1) on pregnant dams and embryo‐fetal development in rats. M + CA was orally administered to pregnant rats from gestational days 6 through 19 at doses of 0, 3, 10, and 30 mg/kg/day of both melamine and cyanuric acid. Maternal toxicity of rats administered 30 mg/kg/day M + CA was manifested as increased incidences of clinical signs and death; gross pathologic findings; higher blood urea nitrogen and creatinine levels; lower body weight gain and food intake; decreased thymus weight; and increased heart, lung, and kidney weights. Histopathological examinations revealed an increase in the incidence of congestion, tubular necrosis/degeneration, crystals, casts, mineralization, inflammatory cells in tubules, tubular dilation, and atrophy of glomeruli in maternal kidneys, whereas fetal kidneys did not show any histopathological changes. Developmental toxicity included a decrease in fetal (28%) and placental weights and a delay in fetal ossification (n = 7). Increased incidence of gross and histopathological changes in the maternal kidney was also found in the middle dose group (n = 12). No treatment‐related maternal or developmental effects were observed in the low dose group (n = 12). Under these experimental conditions, M + CA is embryotoxic at an overt maternotoxic dose in rats and the no‐observed‐adverse‐effect level of M + CA is considered to be 3 mg/kg/day for pregnant dams and 10 mg/kg/day for embryo‐fetal development.